Osteogenic Effects of Aerobic Both Sides Utilized Ball Versus Aerobic Step Training in Premenopausal Women - Anek, Achariya; Mitranun, Witid (Physical Education Theory and Methodology, 2023)
Study purpose. Exercise training plays an important role in increasing bone mass. Nevertheless, the osteogenic effects of exercise training using various bench surfaces are unknown. Therefore, this study aimed to compare the osteogenic effects of exercise with a soft surface bench and an aerobic both sides utilized (BOSU) ball with those of aerobic step exercise training (STEP). Materials and methods. Fifty-two sedentary female participants aged 30–45 years were recruited and randomly divided into three groups. Seventeen participants were in the STEP, 17 in the BOSU, and 18 in the control group. The exercise programs of the STEP and BOSU groups were designed to have the same intensity and heart rate range during each stage of the program. During training, music was used to set the tempo for workouts. Results. After week 24, both training groups showed significant improvements in physical fitness, body composition, and body stability (p<0.05). Increased levels of procollagen type I N-terminal propeptide (P1NP), an osteogenesis marker, were observed in both STEP and BOSU groups. Increased bone mineral density was only seen in the BOSU group (p<0.05). Conclusions. Both STEP and BOSU programs effectively improved P1NP levels, muscle strength, and postural control, but only the aerobic BOSU ball training improved bone mineral density in premenopausal women.